Determinants of women’s labor participation rate: Evidence in ASEAN - Firmansyah, Refly; Purnomo, Didit (Nur Science Institute, 2024)
Attention to women's involvement in the workforce is increasing in social and economic development, particularly in developing countries such as those in ASEAN. However, data indicates that despite progress, the Gender Inequality Index (GII) remains high in ASEAN countries. This condition underscores the importance of focusing specifically on women's empowerment, reproductive health, and participation in the labor market. This research analyzes the influence of wages, women's involvement in parliament, women's life expectancy, fertility rates, and maternal mortality rates on women's labor participation rates in ASEAN. Data for this research was acquired from the World Bank. The study is quantitative, utilizing panel data regression analysis from 2011-2022, covering 11 ASEAN countries, using the Random Effects Model (REM) approach. The research findings indicate that wage, women's life expectancy, fertility rate, and maternal mortality rate variables significantly influence women's labor participation rates in ASEAN from 2011-2022, while women's involvement in parliament does not significantly affect women's labor participation rates. Therefore, ASEAN countries' governments should increase women's wages and healthcare access, promote family planning, support gender equality in education and employment, and enhance women's political participation.